Optimal Timing of Surgery for Intramedullary Cavernous Hemangioma of the Spinal Cord in Relation to Preoperative Motor Paresis, Disease Duration, and Tumor Volume and Location. (May 2017) - Imagama, Shiro; Ito, Zenya; Ando, Kei; Kobayashi, Kazuyoshi; Hida, Tetsuro; Ito, Kenyu; Tsushima, Mikito; Ishikawa, Yoshimoto; Matsumoto, Akiyuki; Morozumi, Masayoshi; Tanaka, Satoshi; Machino, Masaaki; et al.
Study Design: Prospective study. Objective: Investigate factors associated with preoperative motor paresis, recovery, ambulatory status, and intraoperative neurophysiological monitoring (IONM) among patients with no preoperative paresis (N group), complete preoperative motor recovery (CR group), and no complete recovery (NCR group) in patients with intramedullary spinal cavernous hemangioma to determine the optimal timing of surgery. Methods: The study evaluated 41 surgical cases in our institute. Disease duration, tumor lesion, manual muscle testing (MMT), and gait at onset, just before surgery, and final follow-up (FU), tumor and lesion volume, IONM, extent of tumor resection, and tumor recurrence were evaluated among N, CR, and NCR groups. Results: Motor paresis at onset was found in 26 patients (63%), with 42% of those in CR group. Disease duration from onset negatively affected stable gait just before surgery and FU as well as lower preoperative MMT ( P < .05). Thoracic tumors were associated with patients with unstable gait before surgery ( P < .05). Tumor volume was larger in NCR group ( P < .05). IONM significantly decreased in NCR and CR groups than in N group ( P < .05). The NCR group had residual mild motor paresis at FU ( P < .05). Stable gait at FU was similar in N group and CR group, though lower in NCR group ( P < .05). Conclusions: Early surgery is generally recommended for thoracic tumors and large tumors during stable gait without motor paresis before long disease duration. Surgery may be postponed until patients recover from preoperative motor paresis to allow optimal surgical outcome. IONM should be carefully monitored in patients with a history of preoperative paresis even with preoperative complete motor recovery.